Transitions in Project Management Offices: A Framework Relating Functions, Success Factors and Project Performance in a High-Technology Company. Issue 3 (3rd July 2022) - Barbalho, Sanderson César Macêdo; Carlos de Toledo, José; Cintra Faria, Ana Carolina
Abstract: This paper aims to present and analyze the transitions in operational activities and the performance of a Project Management Office (PMO) in a technology-based company through a longitudinal case study. The paper discusses functions, tensions, success factors, indicators, and performance and how they drive the major changes faced by the PMO. The results demonstrated that political tensions, more than performance, explained PMO changes. Tensions are originated from both requirements from project stakeholders that were not addressed and success itself, meaning that stakeholder dispute for capitalizing on the success's honors and benefits. Issues about centralization, project performance, and focus on stakeholders' demands seem to be central for designing the role and functions of project management offices in the studied high-technology company. In the end, a theoretical framework presents the results of the case study in terms of factors influencing PMO transitions.